Nova Escola a revista de quem educa: a fabricação de modelos ideais do ser professor - Ripa, Roselaine (2010)
The Nova Escola magazine is edited by Victor Civita Fundation and counts with subsidies from the Federal Government and from private enterprises. His publications contemplate many subjects related to Education, using for this several forms: interviews, articles, experiential accounts, suggestions for class activities, well succeeded projects presentation, reports, etc. The magazine launching was in 1986, period in which the country redemocratization was trying to be consolidated, with the goals of informing and updating the Brazilian teacher. From 1998, the Nova Escola team started to organize the Victor Civita Prize: Mark 10 Educator , which elects the ones who developed good quality experiences of teaching/learning . Therefore, it becomes opportune to investigate how a magazine, which has a large circulation in the educational field, which receives subsidies from the Federal Government, which is distributed without costs to the whole Brazilian public schools, which considers itself as a necessary instrument so improvements in education can be effective, which calls itself a educational magazine , which is destined for those who educates , and which concedes prizes to the teachers that deserve mark 10, operates in the patterns construction of being teacher . Considering, therefore, the Nova Escola magazine as a communication support integrant of the culture industry, which broadcasts, through its content, the ideas of his producers and his consumers, we elaborated the following research question: how the Nova Escola magazine effected in the ideal patterns construction of being a teacher ? Thus, we have as goals: to map, in the period from 1986 to 2006, the predominant themes in the Nova Escola magazine reports; to establish an interface between the approached themes and the historical context in which the publication occurred; and to analyze the Basic Education teacher representation suggested and/or enrolled in the winner projects of Victor Civita Prize. The mapping register included seven distinct fields, organized in chronological order: magazine number; report title followed by the lead; author/reporter; section in which the report was published; and the following categories: educational experiences, teaching and learning processes, educational policy, and teacher professionalization. From this mapping, the reports that related the projects of the Mark 10 Educator , elected by Victor Civita Prize of each year, were analyzed. To the consecution of the proposed analysis, we elected as references the texts from authors who investigate the facts and historical process of the post-military dictatorship period in Brazil, as well as researches about the teacher identity construction and theoretical studies about culture industry, semi-formation and damaged education, elaborated by the Critical Theory philosophers. In the face of the obtained data, we can detach that the teaching projects sent by those who were elected mark 10 educator are divulged as patterns of being teacher once they develop the educational experiences that are propagated as ideals by the magazine. Those experiences are divulged as imperative prescriptions to the Basic Education teacher who also intend to become a mark 10 educator .